Analisis Harga Saham Sebelum dan Sesudah Merger (PT. Bank Syariah Indonesia Tbk). - Evrina; A. Rozi; Ery Juwita Silalahi (JUMANJI (JURNAL MANAJEMEN JAMBI), 2021)
Sharia banking is one of the nation's economic solutions, this is because economic activity is the backbone of the driving force for national stability, then at this time national economic activities must be started moving towards a sharia-based economy. The development of Islamic banking in Indonesia has resulted in a merger or merger of 3 (three) existing Islamic banks, namely Bank Syariah Mandiri (BSM), Bank Negara Indonesia Syariah (BNIS) and Bank Rakyat Indonesia Syariah (BRIS). The definition of a merger is a process of merging two companies, where one of them remains standing by using the name of the company, while the other company disappears and all of its assets are put into the company that remains standing. There are several types of mergers, including horizontal, vertical and conglomerate mergers. Each merger has its own characteristics. Horizontal merger is a process of merging between two or more companies, where the type of business of the company is still the same. As is happening in the banking industry, of course, the merger is carried out because there are certain goals and reasons to be achieved. Based on some of the problems above, the researcher wants to conduct research on what are the effects or impacts of the merger of three BUMN Sharia Banks on the development of the Islamic economy in Indonesia.